INTERPRETATION OF SYMBOLIC DETAILS IN WESTERN LITERATURE (TAMADDUN NURI JURNALI, 2025)
This article explores the significance, functions, and contributions of symbols in literary works, shedding light on how they enrich narratives and engage readers. Dan Brown's The Da Vinci Code (2003) is a cultural phenomenon that combines art, religion, history, and conspiracy theories. This article examines the intertextual nature of symbols in The Da Vinci Code, analyzing how Brown recontextualizes historical and artistic motifs to reinterpret religious and historical traditions. By studying key symbols such as the Holy Grail, the pentacle, and the Vitruvian Man, Fibbochi sequence, this research highlights the novel's connection to existing texts and its impact on contemporary discourse.